Ultrathin photosensitive resin coating
By applying ultra-thin photosensitive resin coating on the glasses frame, using ion beam spinning and electrostatic field spraying technology, combined with self-assembly of epoxy resin and other photosensitive materials, the existing glasses frame coating is solved, and the photosensitive discoloration and yellowing resistance are achieved, and the service life is extended.
Patent Information
- Application Number
- CN202510028830.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-11
- Publication Date
- 2025-05-27
AI Technical Summary
The existing glasses frame coating materials are prone to aging under ultraviolet rays and oxygen and moisture in the air, resulting in loss of light, color loss, darkness, low aesthetics, poor durability, easy to be affected by sweat and rain, and have a short service life.
A copper fiber membrane is prepared by ion beam-assisted spinning, combined with electrostatic field-assisted spraying technology, a coating with photosensitive and water-oxygen barrier properties is formed. The coating consists of epoxy resin, 3-hydroxy-1-naphthylamine, 5-chloro-1,3,3-trimethyl-2-methylene indoline, 3-aminophthalate and silver chloride. The organic-inorganic composite network structure is formed by self-assembly of spironazine compounds and silver chloride to achieve photosensitive discoloration and yellowing resistance.
The photosensitive color discoloration and yellowing resistance of the glasses frame coating are achieved, which enhances the light fatigue resistance and waterproof oxygen performance of the coating, extends the service life, and improves the aesthetics.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating materials, and specifically relates to an ultra-thin photosensitive resin coating. Background Art
[0002] Most of the existing spectacle frames are of a single color. Some spectacle frames with color-changing functions are only made by spraying thermochromic powder or photochromic powder on the surface of the spectacle frames. Since the color of the spectacle frames themselves is relatively dark, the colors presented after spraying the color-changing powder are not vivid enough, and the color changes are not obvious enough, resulting in low aesthetics. Moreover, the change in temperature is often very slow. For example, when going out, the temperature generally does not change much, and it is very easy to fall off when encountering sweat or rain, resulting in a short service life.
[0003] Since glasses are products that people carry with them, they are often irradiated by outdoor ultraviolet rays and come into contact with oxygen and moisture substances in the air for a long time, resulting in the aging of ordinary spectacle frames. Over time, problems such as loss of luster, loss of color, and dullness will occur, and the surface color will turn yellow. For some light-colored spectacle frames, the yellowing is more obvious, seriously affecting the aesthetics of the glasses and restricting daily use. Summary of the Invention
[0004] The purpose of the present invention is to provide an ultra-thin photosensitive resin coating and its preparation method to solve the problems existing in the prior art.
[0005] To solve the above technical problems, the present invention provides the following technical solution: An ultra-thin photosensitive resin coating, which is obtained by the following method. Ion beam-assisted spinning is used on the spectacle frame to obtain a copper fiber membrane spectacle frame; then, with the copper fiber membrane spectacle frame as the cathode of the electric field and the nozzle as the anode, photosensitive resin is sprayed to obtain a matrix coating; and then electrostatic field-assisted spraying is carried out to obtain a water and oxygen barrier layer.
[0006] Further, the photosensitive resin is prepared from epoxy resin, 3-hydroxy-1-naphthylamine, 5-chloro-1,3,3-trimethyl-2-methylene indoline, 3-aminophthalate, and silver chloride.
[0007] Further, the water and oxygen barrier layer includes an alumina film and a silica film.
[0008] Further, a preparation method of an ultra-thin photosensitive resin coating includes the following preparation steps: (1) Place the pretreated spectacle frame in an ion thinning instrument, evacuate to 3.2×10 -3 ~5.6×10 -3Pa, under an argon atmosphere, bombard for 15 - 27 s at 15 - 23 °, then bombard for 8 - 17 s at 3 - 9 °. After that, using copper paste as the spinning solution, spin to a film layer thickness of 10 - 30 μm, dry at 40 - 50 °C for 4 - 10 h. Then, under a hydrogen atmosphere, heat to 400 - 600 °C at a rate of 2 - 5 °C / min, hold for 2 - 5 h, then heat to 650 - 800 °C at a rate of 1 - 3 °C / min, hold for 1 - 3 h, cool to 500 °C at a rate of 4 - 9 °C / min, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame; (2) Using the copper fiber membrane spectacle frame as the cathode and the nozzle as the anode, spray a photosensitive resin that is 0.3 - 0.7 times the mass of the copper fiber membrane spectacle frame, and cure at 30 - 50 °C for 40 - 50 h to obtain a matrix coating; (3) Place the matrix coating in an electrostatic field with an electric field voltage of 10 - 30 kV, heat to 280 - 330 °C, spray an alumina precursor solution at a rate of 20 - 30 mL / h, with a spraying distance of 30 - 40 mm, spray for 60 - 120 s, intermittent for 180 s, and spray for a total of 12 - 24 min. Then dry at 90 - 120 °C for 4 - 6 h, place in a tubular furnace, react at 300 - 360 °C for 1 - 3 h under a hydrogen atmosphere. Then place it in the same electrostatic field, spray silica sol at the same speed for 10 - 22 min, heat to 100 - 130 °C, dry for 1 - 5 min, and then heat to 400 - 450 °C, hold for 2 - 5 h to obtain an ultra-thin photosensitive resin coating.
[0009] Further, for the pre-treated spectacle frame in step (1): Wash the spectacle frame with acetone and absolute ethanol in turn for 5 - 11 min at 25 - 35 kHz.
[0010] Further, the bombardment energy of the ion thinning instrument in step (1) is 1 - 6 keV, and the argon flow rate is 20 - 30 sccm; the spinning head size is 2 - 3 mm, the flow rate is 22 - 34 mL / min, and the air spacing is 18 - 30 cm.
[0011] Further, for the copper paste in step (1): Mix polyethersulfone, N-methylpyrrolidone, and polyvinylpyrrolidone in a mass ratio of 1:4:0.2 - 1:4:0.4, grind at 14 - 36 rpm for 4 - 9 h, then add copper powder that is 6 - 11 times the mass of polyethersulfone, grind at the same speed for 44 - 50 h, and then evacuate for 33 - 59 min.
[0012] Further, for the photosensitive resin in step (2): A. Mix E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol at a mass ratio of 1:0.3:0.2 to 1:0.5:0.3. Under nitrogen protection, heat to 60 - 75°C, stir until dissolved, then add 3-hydroxy-1-naphthylamine in an amount 0.4 - 0.7 times the mass of E-44 epoxy resin. After reacting for 12 - 15 h, add an ethanol aqueous solution in an amount 0.6 - 2.1 times the mass of E-44 epoxy resin. The mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:1. Let it stand for 18 - 34 min to obtain a photosensitive resin matrix. B. Mix the photosensitive resin matrix, sodium hydroxide, and deionized water at a mass ratio of 1:0.3:8 to 1:0.6:15. Cool to -5 - 0°C in a salt bath, then add sodium nitrite in an amount 0.4 - 0.7 times the mass of the photosensitive resin matrix. While stirring at 50 - 100 rpm, add sulfuric acid with a mass fraction of 42% in an amount 2 - 6 times the mass of the photosensitive resin matrix. After reacting for 57 - 71 min, perform suction filtration, wash with deionized water until the solution pH is 6 - 7, then add methanol in an amount 21 - 30 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat to 66 - 80°C, then add 5-chloro-1,3,3-trimethyl-2-methyleneindoline in an amount 0.6 - 1.3 times the mass of the photosensitive resin matrix. After reacting for 8 - 14 h, concentrate at 200 - 300 rpm and 60 - 80°C for 2 - 4 h to obtain a spirooxazine compound. Mix 3-aminophthalate, pyridine, and the spirooxazine compound at a mass ratio of 1:6:1 to 1:14:2. Stir at 100 - 200 rpm for 6 - 10 h, then concentrate at a vacuum of 0.04 - 0.08 MPa and 80 - 100°C for 2 - 5 h. Then wash successively with ethyl acetate, distilled water, and saturated brine 5 - 10 times, and dry at 40 - 60°C for 5 - 10 h to obtain a modified resin. C. Mix the modified resin with methanol in an amount 4 - 10 times the mass of the modified resin. At 20 - 30°C, add ammonia water with a mass fraction of 25 - 28% in an amount 0.7 - 1.4 times the mass of the modified resin at a rate of 0.5 - 1.5 mL / min. Stir and react at 50 - 100 rpm for 6 - 9 h, then cool to 0 - 5°C and keep warm for 0.5 - 1.5 h. Filter, then add triethylamine in an amount 1.0 - 2.1 times the mass of the modified resin and tetrahydrofuran in an amount 4 - 8 times the mass of the modified resin. After mixing evenly, cool to -10 - 0°C, add trifluoroacetic anhydride in an amount 1.2 - 2.6 times the mass of the modified resin at a rate of 0.6 - 1.2 mL / min, and keep warm and react at -10 - 0°C for 58 - 71 min. Then heat to 30 - 40°C and keep warm and react for 2 - 5 h. Distill at a vacuum of 0.04 - 0.08 MPa and 50 - 65°C for 3 - 6 h. Then add deionized water in an amount 2 - 4 times the amount of the modified resin and ethyl acetate in an amount 3 - 6 times the mass of the modified resin. Separate the liquid, wash with distilled water 3 - 7 times, and distill at a vacuum of 0.05 - 0.1 MPa and 60 - 71°C for 2 - 4 h to obtain a nitrile compound. D. Mix a nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.3:5:0.001 to 1:0.6:9:0.001. After microwave heating at 180 - 310 °C for 8 - 20 min, wash successively with deionized water, absolute ethanol, and acetone 4 - 10 times, centrifuge at 8000 - 10000 rpm for 1 - 5 min, filter, and dry at 60 - 73 °C for 2 - 6 h to obtain a preliminary photosensitive resin. Mix the preliminary photosensitive resin, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene in a mass ratio of 1:0.08:0.6:0.6 to 1:0.22:0.9:0.9 to obtain a photosensitive resin.
[0013] Further, the aluminum oxide precursor solution in step (3): Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:8:3 to 1:13:7 to obtain an aluminum oxide precursor solution.
[0014] Further, the silica sol in step (3): Mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:1:0.2:0.02 to 1:2:1.0:0.05, heat to 50 - 60 °C, and reflux for 3 - 5 h to obtain a tetraethyl orthosilicate mixture. Add absolute ethanol with a volume 17 - 20 times that of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention uses a photosensitive resin as the base material and coats a water and oxygen barrier layer, thereby preparing a coating for spectacle frames to achieve the effects of photosensitive color change and yellowing resistance.
[0016] First, utilize the ring-opening reaction of the amino group of 3-hydroxy-1-naphthylamine with epoxy resin and graft it into the epoxy resin molecule. Then, under the action of sodium nitrite, introduce a nitroso group at the ortho-position of the hydroxyl group and form a spirooxazine compound by cyclization with 5-chloro-1,3,3-trimethyl-2-methyleneindoline, endowing the coating with photosensitivity. Moreover, the polyhydroxy characteristics of epoxy resin can increase the polarity of the spirooxazine compound, and there are more hydrogen bonds between molecules, making its rigidity increase and the photo-induced ring-opening body more stable, thus prolonging the photosensitive life of the coating. Next, the amino group of 3-aminophthalate combines with the chloride ion of the spirooxazine compound. After its ester group undergoes amidation and nitrilation, it coordinates with silver chloride and self-assembles into an organic-inorganic amorphous composite network structure and is embedded therein to obtain a photosensitive resin. Under the further induction of light, the photo-induced ring-opening organic matter undergoes intermolecular transition to generate colored free radicals, which promote the oxidation and valence change of silver ions, achieving a color-changing effect, enabling the color of the spectacle frame body coated with this coating to change with the change of light intensity, increasing the interestingness. At the same time, the addition of silver ions can improve the light fatigue resistance of the coating, and it can also fade quickly in an air-insulated environment.
[0017] Secondly, in the present invention, copper powder is used as a raw material to form a copper fiber film on the spectacle frame by spinning. Before spinning, the spectacle frame is bombarded with an ion beam. Relying on the huge energy transmitted by the incident particles, the surface atomic activity is activated, and lattice depressions appear on the surface part, enabling the copper fiber film to be embedded in the spectacle frame. Taking this as the cathode of the electric field and connecting the anode to the nozzle, a high-voltage electrostatic field is formed to ionize the photosensitive resin, and thus it is electrodeposited on the surface of the spectacle frame to form a continuous structure, with a uniform, continuous and dense surface. At the same time, when the surface of the photosensitive resin dries and cures, water evaporation generates pores, forming an uneven structure with the metal particles in the photosensitive resin, increasing the surface roughness of the coating, endowing the coating with good hydrophobicity, isolating the contact of water vapor with the metal frame, and enabling the coating to have a yellowing resistance effect. Then, using the electrostatic field-assisted spraying method, an alumina precursor solution and a silica sol are sprayed in sequence to form charged particles, which decompose in the gas phase and deposit on the surface of the photosensitive resin, and film formation is carried out in a layer-by-layer growth manner. The existence of the layered structure will increase the path for small molecules such as water and oxygen to diffuse in the film layer, prolong the penetration time of small molecules, thereby achieving a barrier effect and improving the yellowing resistance effect of the coating. Detailed implementation manners
[0018] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.
[0019] The method provided by the present invention is described in detail through the following embodiments. The test methods for each index of the ultra-thin photosensitive resin coating prepared in the following embodiments are as follows: Photosensitive color change property: Take the same mass of the examples and the comparative examples for testing the photosensitive color change effect. After irradiating with ultraviolet light of 365 nm for 3 minutes, observe whether there is color change.
[0020] Photosensitive color change fatigue property: Take the same mass of the examples and the comparative examples for testing the photosensitive color change fatigue effect. Continuously irradiate with ultraviolet light of 365 nm for 8 hours, with an interval of 10 hours, and cycle 5 times, then observe whether there is color change.
[0021] Yellowing resistance: Take the same mass of the examples and the comparative examples for testing the yellowing resistance effect. Place the specimen in a pure oxygen environment with a relative humidity of 90% for 30 days, and observe whether the surface turns yellow.
[0022] Example 1 A preparation method of an ultra-thin photosensitive resin coating, the preparation method of the ultra-thin photosensitive resin coating includes the following preparation steps: (1) At 25 kHz, wash the spectacle frame with acetone and absolute ethanol in sequence for 11 minutes to obtain a pretreated spectacle frame; place the pretreated spectacle frame in an ion thinning instrument with a bombardment energy of 1 keV, evacuate to 3.2×10 -3 Pa, introduce argon at 20 sccm, under the argon atmosphere, bombard at 15° for 15 s, and then bombard at 3° for 8 s; mix polyethersulfone, N-methylpyrrolidone and polyvinylpyrrolidone according to a mass ratio of 1:4:0.2, grind at 14 rpm for 9 hours, add copper powder 6 times the mass of polyethersulfone, grind at the same speed for 50 hours, and then evacuate for 33 minutes to obtain copper paste; use the copper paste as the spinning solution, spin to a film layer thickness of 10 μm, dry at 40°C for 10 hours, under a hydrogen atmosphere, heat up to 400°C at a rate of 2°C / min, keep warm for 5 hours, then heat up to 650°C at a rate of 1°C / min, keep warm for 3 hours, cool down to 500°C at a rate of 4°C / min, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame; during the spinning process, the spinning head size is 2 mm, the flow rate is 22 mL / min, and the air spacing is 18 cm; (2) Mix E-44 epoxy resin, ethylene glycol monobutyl ether and absolute ethanol according to a mass ratio of 1:0.3:0.23, under nitrogen protection, heat up to 60°C, stir until dissolved, add 3-hydroxy-1-naphthylamine 0.4 times the mass of E-44 epoxy resin, react for 12 hours, then add an ethanol aqueous solution 0.6 times the mass of E-44 epoxy resin, and the mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:1, and let it stand for 18 minutes to obtain a photosensitive resin matrix; (3) Mix the photosensitive resin matrix, sodium hydroxide, and deionized water in a mass ratio of 1:0.3:8, cool in a salt bath to -5°C, then add sodium nitrite which is 0.4 times the mass of the photosensitive resin matrix. While stirring at 50 rpm, add sulfuric acid with a mass fraction of 42% which is 2 times the mass of the photosensitive resin matrix. After reacting for 57 min, perform suction filtration, wash with deionized water until the solution pH is 6, then add methanol which is 21 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat to 66°C, then add 5-chloro-1,3,3-trimethyl-2-methyleneindoline which is 0.6 times the mass of the photosensitive resin matrix. After reacting for 8 h, concentrate at 200 rpm and 60°C for 4 h to obtain the spirooxazine compound; Mix 3-aminophthalate, pyridine, and the spirooxazine compound in a mass ratio of 1:6:1, stir at 100 rpm for 10 h, then concentrate at a vacuum of 0.04 MPa and 80°C for 2 h, and then wash 5 times successively with ethyl acetate, distilled water, and saturated brine, and dry at 40°C for 10 h to obtain the modified resin; (4) Mix the modified resin and methanol which is 4 times the mass of the modified resin. At 20°C, add ammonia water with a mass fraction of 25% which is 0.7 times the mass of the modified resin at a rate of 0.5 mL / min. Stir and react at 50 rpm for 9 h, then cool to 0°C and keep warm for 0.5 h, filter, then add triethylamine which is 1.0 times the mass of the modified resin and tetrahydrofuran which is 4 times the mass of the modified resin. After mixing evenly, cool to -10°C, add trifluoroacetic anhydride which is 1.2 times the mass of the modified resin at a rate of 0.6 mL / min, keep warm and react at -10°C for 58 min, then heat to 30°C and keep warm and react for 5 h, distill at a vacuum of 0.04 MPa and 50°C for 3 h, then add deionized water which is 2 times the mass of the modified resin and ethyl acetate which is 3 times the mass of the modified resin, separate the liquid, wash 3 times with distilled water, and distill at a vacuum of 0.05 MPa and 60°C for 2 h to obtain the nitrile compound; (5) Mix the nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.3:5:0.001. After microwave heating at 180°C for 20 min, wash 4 times successively with deionized water, absolute ethanol, and acetone, centrifuge at 8000 rpm for 5 min, filter, and dry at 60°C for 6 h to obtain the initial photosensitive resin material; Mix the initial photosensitive resin material, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene according to a mass ratio of 1:0.08:0.6:0.6~ to obtain the photosensitive resin; (6) Use the copper fiber membrane eyeglass frame as the cathode and the nozzle as the anode, spray the photosensitive resin which is 0.3 times the mass of the copper fiber membrane eyeglass frame, and cure at 30°C for 50 h to obtain the matrix coating; (7) Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:8:3 to obtain an alumina precursor solution; place the substrate coating in an electrostatic field with an electric field voltage of 10 kV, heat it to 280 °C, spray the alumina precursor solution at a rate of 20 mL / h, with a spraying distance of 30 mm, spray for 60 s, intermittent for 180 s, after spraying for a total of 24 min, dry at 90 °C for 6 h, place it in a tube furnace, react at 300 °C for 3 h under a hydrogen atmosphere; mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:1:0.2:0.02, heat to 50 °C, reflux for 5 h to obtain a tetraethyl orthosilicate mixture; add absolute ethanol 17 times the volume of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol, then place it in the same electrostatic field, spray the silica sol at the same speed, spray for 22 min, heat up to 100 °C, dry for 5 min, then heat up to 400 °C, and keep warm for 5 h to obtain an ultra-thin photosensitive resin coating.
[0023] Example 2 A method for preparing an ultra-thin photosensitive resin coating, the method for preparing the ultra-thin photosensitive resin coating includes the following preparation steps: (1) At 30 kHz, wash the spectacle frame with acetone and absolute ethanol in sequence for 8 min to obtain a pretreated spectacle frame; place the pretreated spectacle frame in an ion thinning instrument with a bombardment energy of 3 keV, evacuate to 4.4×10 -3 Pa, introduce argon at 25 sccm, under an argon atmosphere, bombard at 19° for 21 s, and then bombard at 6° for 12 s; mix polyethersulfone, N-methylpyrrolidone, and polyvinylpyrrolidone in a mass ratio of 1:4:0.3, grind at 25 rpm for 6.5 h, add copper powder 8.5 times the mass of polyethersulfone, grind at the same speed for 47 h, and evacuate for 46 min to obtain a copper paste; use the copper paste as a spinning solution, spin to a film layer thickness of 230 μm, dry at 45 °C for 7 h, then under a hydrogen atmosphere, heat up to 500 °C at a rate of 3 °C / min, keep warm for 3.5 h, then heat up to 725 °C at a rate of 2 °C / min, keep warm for 2 h, and cool down to 500 °C at a rate of 6 °C / min, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame; during the spinning process, the size of the spinneret is 3 mm, the flow rate is 28 mL / min, and the air gap is 24 cm; (2) Mix E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol in a mass ratio of 1:0.4:0.25, under nitrogen protection, heat up to 68 °C, stir until dissolved, add 3-hydroxy-1-naphthylamine 0.55 times the mass of E-44 epoxy resin, react for 13.5 h, then add an ethanol aqueous solution 1.35 times the mass of E-44 epoxy resin, the mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:1, and let it stand for 26 min to obtain a photosensitive resin matrix; (3) Mix the photosensitive resin matrix, sodium hydroxide, and deionized water in a mass ratio of 1:0.45:11.5, cool the salt bath to -2°C, then add sodium nitrite with a mass 0.55 times that of the photosensitive resin matrix. Under stirring at 70 rpm, add sulfuric acid with a mass fraction of 42% and a mass 4 times that of the photosensitive resin matrix. After reacting for 64 min, perform suction filtration, wash with deionized water until the solution pH is 6.5, then add methanol with a mass 25.5 times that of the photosensitive resin matrix. Under nitrogen protection, heat to 73°C, and then add 5-chloro-1,3,3-trimethyl-2-methyleneindoline with a mass 0.95 times that of the photosensitive resin matrix. After reacting for 11 h, concentrate at 250 rpm and 70°C for 3 h to obtain the spirooxazine compound; Mix 3-aminophthalate, pyridine, and the spirooxazine compound in a mass ratio of 1:10:1.5, stir at 150 rpm for 8 h, then concentrate at a vacuum degree of 0.06 MPa and 90°C for 3 h, and then wash successively with ethyl acetate, distilled water, and saturated brine 7 times, and dry at 50°C for 7.5 h to obtain the modified resin; (4) Mix the modified resin and methanol with a mass 7 times that of the modified resin. At 25°C, add ammonia water with a mass fraction of 26% and a mass 1.05 times that of the modified resin at a rate of 1.0 mL / min. Stir and react at 70 rpm for 7.5 h, then cool to 2°C, keep warm for 1 h, filter, then add triethylamine with a mass 1.55 times that of the modified resin and tetrahydrofuran with a mass 6 times that of the modified resin. After mixing evenly, cool to -5°C, add trifluoroacetic anhydride with a mass 1.9 times that of the modified resin at a rate of 0.9 mL / min, keep warm and react at -5°C for 64 min, then heat to 35°C, keep warm and react for 3.5 h, distill at a vacuum degree of 0.06 MPa and 58°C for 4.5 h, then add deionized water with a mass 3 times that of the modified resin and ethyl acetate with a mass 4.5 times that of the modified resin, separate the liquid, wash with distilled water 5 times, and distill at a vacuum degree of 0.08 MPa and 66°C for 3 h to obtain the nitrile compound; (5) Mix the nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.45:7:0.001. After microwave heating at 245°C for 14 min, wash successively with deionized water, absolute ethanol, and acetone 7 times, centrifuge at 9000 rpm for 3 min, filter, and dry at 67°C for 4 h to obtain the preliminary photosensitive resin; Mix the preliminary photosensitive resin, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene in a mass ratio of 1:0.15:0.75:0.75 to obtain the photosensitive resin; (6) Use a copper fiber membrane eyeglass frame as the cathode and a nozzle as the anode, spray the photosensitive resin with a mass 0.5 times that of the copper fiber membrane eyeglass frame, and cure at 40°C for 45 h to obtain the matrix coating; (7) Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:10.5:5 to obtain an alumina precursor solution; place the substrate coating in an electrostatic field with an electric field voltage of 20 kV, heat it to 305 °C, spray the alumina precursor solution at a rate of 25 mL / h, with a spraying distance of 35 mm, spray for 90 s, intermittent for 180 s, after spraying for a total of 18 min, dry it at 105 °C for 5 h, place it in a tube furnace, react at 330 °C for 2 h under a hydrogen atmosphere; mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:1.5:0.6:0.035, heat it to 55 °C, reflux for 4 h to obtain a tetraethyl orthosilicate mixture; add absolute ethanol with a volume 18.5 times that of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol, then place it in the same electrostatic field and spray the silica sol at the same speed, spray for 16 min, heat up to 115 °C, dry for 3 min, then heat up to 425 °C, and keep warm for 3.5 h to obtain an ultrathin photosensitive resin coating.
[0024] Example 3 A method for preparing an ultrathin photosensitive resin coating, the method for preparing the ultrathin photosensitive resin coating includes the following preparation steps: (1) At 35 kHz, wash the spectacle frame with acetone and absolute ethanol in sequence for 5 min to obtain a pretreated spectacle frame; place the pretreated spectacle frame in an ion thinning instrument with a bombardment energy of 6 keV, evacuate to 5.6×10 -3 Pa, introduce argon at 30 sccm, under an argon atmosphere, bombard at 23° for 27 s, and then bombard at 9° for 17 s; mix polyethersulfone, N-methylpyrrolidone, and polyvinylpyrrolidone in a mass ratio of 1:4:0.4, grind at 36 rpm for 4 h, add copper powder with a mass 11 times that of polyethersulfone, grind at the same speed for 44 h, and then evacuate for 59 min to obtain a copper paste; use the copper paste as the spinning solution, spin to a film layer thickness of 30 μm, dry at 50 °C for 4 h, under a hydrogen atmosphere, heat up to 600 °C at a rate of 5 °C / min, keep warm for 2 h, then heat up to 800 °C at a rate of 3 °C / min, keep warm for 1 h, cool down to 500 °C at a rate of 9 °C / min, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame; during the spinning process, the size of the spinneret is 3 mm, the flow rate is 34 mL / min, and the air gap is 30 cm; (2) Mix E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol in a mass ratio of 1:0.5:0.3, under nitrogen protection, heat up to 75 °C, stir until dissolved, add 3-hydroxy-1-naphthylamine with a mass 0.7 times that of E-44 epoxy resin, react for 15 h, then add an ethanol aqueous solution with a mass 2.1 times that of E-44 epoxy resin, the mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:1, and let it stand for 34 min to obtain a photosensitive resin matrix; (3) Mix the photosensitive resin matrix, sodium hydroxide, and deionized water in a mass ratio of 1:0.6:15, cool it in a salt bath to 0 °C, then add sodium nitrite in an amount 0.7 times the mass of the photosensitive resin matrix. While stirring at 100 rpm, add sulfuric acid with a mass fraction of 42% in an amount 6 times the mass of the photosensitive resin matrix. After reacting for 71 min, perform suction filtration, wash with deionized water until the solution pH is 7, then add methanol in an amount 30 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat to 80 °C, then add 5-chloro-1,3,3-trimethyl-2-methyleneindoline in an amount 1.3 times the mass of the photosensitive resin matrix. After reacting for 14 h, concentrate at 300 rpm and 80 °C for 2 h to obtain a spirooxazine compound; Mix 3-aminophthalate, pyridine, and the spirooxazine compound in a mass ratio of 1:14:2, stir at 200 rpm for 6 h, then concentrate at a vacuum of 0.08 MPa and 100 °C for 5 h, and then wash 10 times with ethyl acetate, distilled water, and saturated brine successively, and dry at 60 °C for 5 h to obtain a modified resin; (4) Mix the modified resin and methanol in an amount 10 times the mass of the modified resin. At 30 °C, add ammonia water with a mass fraction of 28% in an amount 1.4 times the mass of the modified resin at a rate of 1.5 mL / min. Stir and react at 100 rpm for 6 h, then cool to 5 °C and keep warm for 1.5 h, filter, then add triethylamine in an amount 2.1 times the mass of the modified resin and tetrahydrofuran in an amount 8 times the mass of the modified resin. After mixing evenly, cool to 0 °C, add trifluoroacetic anhydride in an amount 2.6 times the mass of the modified resin at a rate of 1.2 mL / min, keep warm and react at 0 °C for 71 min, then heat to 40 °C and keep warm and react for 2 h. Distill at a vacuum of 0.08 MPa and 65 °C for 6 h, then add deionized water in an amount 4 times the mass of the modified resin and ethyl acetate in an amount 6 times the mass of the modified resin, separate the liquid, wash 7 times with distilled water, and distill at a vacuum of 0.1 MPa and 71 °C for 4 h to obtain a nitrile compound; (5) Mix the nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.6:9:0.001, microwave heat at 310 °C for 8 min, then wash 10 times with deionized water, absolute ethanol, and acetone successively, centrifuge at 10000 rpm for 1 min, filter, and dry at 73 °C for 2 h to obtain a preliminary photosensitive resin; Mix the preliminary photosensitive resin, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene in a mass ratio of 1:0.22:0.9:0.9 to obtain a photosensitive resin; (6) Use a copper fiber membrane spectacle frame as the cathode and a nozzle as the anode, spray the photosensitive resin in an amount 0.7 times the mass of the copper fiber membrane spectacle frame, and cure at 50 °C for 40 h to obtain a matrix coating; (7) Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:13:7 to obtain an alumina precursor solution; place the substrate coating in an electrostatic field with an electric field voltage of 30 kV, heat it to 330 °C, spray the alumina precursor solution at a rate of 30 mL / h, with a spraying distance of 40 mm, spray for 120 s, intermittent for 180 s, after spraying for a total of 12 min, dry at 120 °C for 4 h, place it in a tubular furnace, and react at 360 °C for 1 h under a hydrogen atmosphere; mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:2:1.0:0.05, heat to 60 °C, and reflux for 3 h to obtain a tetraethyl orthosilicate mixture; add absolute ethanol 20 times the volume of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol, then place it in the same electrostatic field and spray the silica sol at the same speed for 10 min, heat up to 130 °C, dry for 2 min, and then heat up to 450 °C and hold for 2 h to obtain an ultra-thin photosensitive resin coating.
[0025] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is only in step (2). Modify step (2) as follows: Mix E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol in a mass ratio of 1:0.4:0.25, heat to 68 °C under nitrogen protection, and stir until dissolved to obtain a photosensitive resin matrix. The remaining preparation steps are the same as those in Example 2.
[0026] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is only in step (3). Modify step (3) as follows: Mix 3-aminophthalate, pyridine, and the photosensitive resin matrix in a mass ratio of 1:10:1.5, stir at 150 rpm for 8 h, then concentrate at a vacuum of 0.06 MPa and 90 °C for 3 h, and then wash 7 times with ethyl acetate, distilled water, and saturated brine successively, dry at 50 °C for 7.5 h to obtain a modified resin. The remaining preparation steps are the same as those in Example 2.
[0027] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that steps (4) and (5) are absent. Modify step (3) as follows: Mix the photosensitive resin matrix, sodium hydroxide, and deionized water in a mass ratio of 1:0.45:11.5, cool to -2 °C in a salt bath, then add sodium nitrite 0.55 times the mass of the photosensitive resin matrix, stir at 70 rpm, add sulfuric acid with a mass fraction of 42% 4 times the mass of the photosensitive resin matrix, react for 64 min, then filter, wash with deionized water until the solution pH is 6.5, then add methanol 25.5 times the mass of the photosensitive resin matrix, heat to 73 °C under nitrogen protection, and then add 5-chloro-1,3,3-trimethyl-2-methyleneindoline 0.95 times the mass of the photosensitive resin matrix, react for 11 h, and then concentrate at 250 rpm and 70 °C for 3 h to obtain a photosensitive resin. The remaining preparation steps are the same as those in Example 2.
[0028] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that steps (1) and (6) are absent, and step (7) is changed to: spraying a photosensitive resin 0.5 times the mass of the spectacle frame onto the spectacle frame to obtain a matrix coating; mixing aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:13:7 to obtain an alumina precursor solution; placing the matrix coating in an electrostatic field with an electric field voltage of 30 kV, heating to 330 °C, spraying the alumina precursor solution at a rate of 30 mL / h, with a spraying distance of 40 mm, spraying for 120 s, intermittent for 180 s, after spraying for a total of 12 min, drying at 120 °C for 4 h, placing it in a tubular furnace, reacting at 360 °C for 1 h under a hydrogen atmosphere; mixing tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:2:1.0:0.05, heating to 60 °C, refluxing for 3 h to obtain a tetraethyl orthosilicate mixture; adding absolute ethanol 20 times the volume of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol, then placing it in the same electrostatic field and spraying the silica sol at the same speed, spraying for 10 min, heating to 130 °C, drying for 2 min, then heating to 450 °C, and holding for 2 h to obtain an ultra-thin photosensitive resin coating. The remaining preparation steps are the same as those in Example 2.
[0029] Comparative Example 5 The difference between Comparative Example 5 and Example 2 lies in the difference in step (1). Step (1) is changed to: washing the spectacle frame with acetone and absolute ethanol successively for 8 min at 30 kHz to obtain a pretreated spectacle frame; mixing polyethersulfone, N-methylpyrrolidone, and polyvinylpyrrolidone in a mass ratio of 1:4:0.3, grinding for 6.5 h at 25 rpm, adding copper powder 8.5 times the mass of polyethersulfone, grinding at the same speed for 47 h, and then evacuating for 46 min to obtain a copper paste; using the copper paste as a spinning solution, spinning to a film layer thickness of 230 μm, drying at 45 °C for 7 h, then in a hydrogen atmosphere, heating to 500 °C at a rate of 3 °C / min, holding for 3.5 h, then heating to 725 °C at a rate of 2 °C / min, holding for 2 h, and then cooling to 500 °C at a rate of 6 °C / min and then naturally cooling to room temperature to obtain a copper fiber membrane spectacle frame; during the spinning process, the size of the spinneret is 3 mm, the flow rate is 28 mL / min, and the air gap is 24 cm. The remaining preparation steps are the same as those in Example 2.
[0030] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is only that step (7) is absent, and the remaining preparation steps are the same as those in Example 2.
[0031] Effect Example Table 1 below gives the performance analysis results of the ultra-thin photosensitive resin coatings of Examples 1 to 3 and Comparative Examples 1 to 6 of the present invention.
[0032] Table 1 Color change under ultraviolet light Color change under long-term ultraviolet light Yellowing situation Example 1 Color change Color change No yellowing Example 2 Color change Color change No yellowing Example 3 Color change Color change No yellowing Comparative example 1 No change No change No yellowing Comparative example 2 No change No change No yellowing Comparative example 3 No change No change Slight yellowing Comparative example 4 Color change Color change Yellowing Comparative example 5 Color change Color change Yellowing Comparative example 6 Color change Color change Yellowing From the comparison of the experimental data on the color change under ultraviolet light and the color change over a long time between the examples and the comparative examples, it can be found that this product uses 3-hydroxy-1-naphthylamine and 5-chloro-1,3,3-trimethyl-2-methylene indoline to modify epoxy resin, introducing a spirooxazine group into the epoxy resin molecular chain, making the coating photosensitive. Moreover, the polyhydroxy characteristics of epoxy resin can improve the polarity of the spirooxazine group, increase the rigidity, and extend the light fatigue resistance of the coating. Then, it is further modified with 3-aminophthalate and coordinated with silver chloride. Under the further induction of light, intermolecular transition occurs, generating colored free radicals, promoting the oxidation and valence change of silver ions to achieve the color change effect. At the same time, the addition of silver ions can improve the light fatigue resistance of the coating. From the comparison of the experimental data on the yellowing situation between the examples and the comparative examples, it can be found that this product first bombards and roughens the spectacle frame by ion beam, which is beneficial for the copper fiber film to be embedded on the surface during the spinning process, so as to act as the cathode of the electrode. Utilizing the electric field effect, the photosensitive resin is electrodeposited on the surface of the spectacle frame to fill the depressions, thus being closely connected. And when curing, the pores remaining after the evaporation of moisture form a rough surface with metal ions, making the coating hydrophobic and able to isolate moisture substances. Then, using the electrostatic field-assisted spraying method, alumina and silica films are grown layer by layer on the surface to block the penetration of moisture and oxygen, effectively isolating water and oxygen, and improving the yellowing resistance effect of the coating.
[0033] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and without departing from the spirit or basic characteristics of the present invention, the present invention can be implemented in other specific forms. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, it is intended to include all changes falling within the meaning and scope of the equivalent elements of the claims in the present invention. Any reference signs in the claims should not be construed as limiting the claimed rights.
Claims
1. An ultra-thin photosensitive resin coating, characterized in that, the ultra-thin photosensitive resin coating is prepared by the following method: using ion beam assisted spinning on the spectacle frame to obtain a copper fiber membrane spectacle frame; then taking the copper fiber membrane spectacle frame as the cathode of the electric field and the nozzle as the anode to spray the photosensitive resin to obtain a matrix coating; and then carrying out electrostatic field assisted spraying to obtain a water and oxygen barrier layer; the preparation method of the ultra-thin photosensitive resin coating comprises the following preparation steps: The preparation method of the photosensitive resin is as follows: at 30 kHz, wash the spectacle frame with acetone and absolute ethanol in sequence for 8 min to obtain a pretreated spectacle frame; place the pretreated spectacle frame in an ion thinning instrument with a bombardment energy of 3 keV, evacuate to 4.4×10 -3 Pa, introduce argon at 25 sccm, under an argon atmosphere, bombard at 19° for 21 s, and then bombard at 6° for 12 s; mix polyethersulfone, N-methylpyrrolidone and polyvinylpyrrolidone in a mass ratio of 1:4:0.3, grind at 25 rpm for 6.5 h, add copper powder 8.5 times the mass of polyethersulfone, grind at the same speed for 47 h, and then evacuate for 46 min to obtain a copper paste; use the copper paste as a spinning solution, spin to a film thickness of 230 μm, dry at 45 °C for 7 h, under a hydrogen atmosphere, heat up to 500 °C at a rate of 3 °C / min, hold for 3.5 h, then heat up to 725 °C at a rate of 2 °C / min, hold for 2 h, cool down to 500 °C at a rate of 6 °C / min, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame; during the spinning process, the spinning head size is 3 mm, the flow rate is 28 mL / min, and the air gap is 24 cm; Mix E-44 epoxy resin, ethylene glycol monobutyl ether and absolute ethanol according to a mass ratio of 1:0.4:0.
25. Under nitrogen protection, heat up to 68 °C, stir until dissolved, then add 3-hydroxy-1-naphthylamine which is 0.55 times the mass of E-44 epoxy resin. After reacting for 13.5 h, add an ethanol aqueous solution which is 1.35 times the mass of E-44 epoxy resin, and the mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:
1. Let it stand for 26 min to obtain a photosensitive resin matrix; Mix the photosensitive resin matrix, sodium hydroxide and deionized water according to a mass ratio of 1:0.45:11.
5. Cool it to -2 °C in a salt bath, then add sodium nitrite which is 0.55 times the mass of the photosensitive resin matrix. Under stirring at 70 rpm, add sulfuric acid with a mass fraction of 42% which is 4 times the mass of the photosensitive resin matrix. After reacting for 64 min, carry out suction filtration, wash it with deionized water until the solution pH is 6.5, then add methanol which is 25.5 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat up to 73 °C, then add 5-chloro-1,3,3-trimethyl-2-methylene indoline which is 0.95 times the mass of the photosensitive resin matrix. After reacting for 11 h, concentrate it at 250 rpm and 70 °C for 3 h to obtain a spirooxazine compound; Mix 3-aminophthalate, pyridine and the spirooxazine compound according to a mass ratio of 1:10:1.
5. Stir at 150 rpm for 8 h, then concentrate it at a vacuum degree of 0.06 MPa and 90 °C for 3 h, and then wash it 7 times successively with ethyl acetate, distilled water and saturated brine, and dry it at 50 °C for 7.5 h to obtain a modified resin; Mix the modified resin and methanol which is 7 times the mass of the modified resin. At 25 °C, add ammonia water with a mass fraction of 26% which is 1.05 times the mass of the modified resin at a rate of 1.0 mL / min. Stir and react at 70 rpm for 7.5 h, then cool it to 2 °C and keep it warm for 1 h, filter it, then add triethylamine which is 1.55 times the mass of the modified resin and tetrahydrofuran which is 6 times the mass of the modified resin, mix them evenly, then cool it to -5 °C, add trifluoroacetic anhydride which is 1.9 times the mass of the modified resin at a rate of 0.9 mL / min, keep it warm and react at -5 °C for 64 min, then heat it up to 35 °C and keep it warm and react for 3.5 h. Distill it at a vacuum degree of 0.06 MPa and 58 °C for 4.5 h, then add deionized water which is 3 times the mass of the modified resin and ethyl acetate which is 4.5 times the mass of the modified resin, separate the liquid, wash it 5 times with distilled water, and distill it at a vacuum degree of 0.08 MPa and 66 °C for 3 h to obtain a nitrile compound; A nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene were mixed in a mass ratio of 1:0.45:7:0.
001. After microwave heating at 245 °C for 14 min, it was washed 7 times successively with deionized water, absolute ethanol, and acetone, centrifuged at 9000 rpm for 3 min, filtered, and dried at 67 °C for 4 h to obtain a preliminary photosensitive resin material; the preliminary photosensitive resin material, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene were mixed in a mass ratio of 1:0.15:0.75:0.75 to obtain a photosensitive resin; Using a copper fiber membrane eyeglass frame as the cathode and a nozzle as the anode, a photosensitive resin 0.5 times the mass of the copper fiber membrane eyeglass frame was sprayed, and cured at 40 °C for 45 h to obtain a matrix coating; Aluminum nitrate, urea, and sodium chloride were mixed in a mass ratio of 1:10.5:5 to obtain an alumina precursor solution; The matrix coating was placed in an electrostatic field with an electric field voltage of 20 kV, heated to 305 °C, and the alumina precursor solution was sprayed at a rate of 25 mL / h, with a spraying distance of 35 mm, sprayed for 90 s, intermittent for 180 s, and sprayed for a total of 18 min. Then it was dried at 105 °C for 5 h, placed in a tube furnace, and reacted at 330 °C for 2 h under a hydrogen atmosphere; tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% were mixed in a mass ratio of 1:1.5:0.6:0.035, heated to 55 °C, and refluxed for 4 h to obtain a tetraethyl orthosilicate mixture; absolute ethanol 18.5 times the volume of the tetraethyl orthosilicate mixture was added to the tetraethyl orthosilicate mixture to obtain a silica sol. Then it was placed in the same electrostatic field and sprayed with the silica sol at the same speed for 16 min, heated to 115 °C, dried for 3 min, and then heated to 425 °C and held for 3.5 h to obtain an ultra-thin photosensitive resin coating.